American graphic : disgust and data in contemporary literature - Clark, Rebecca (Rebecca Bennett) (Stanford University Press, 2023)
"What do we really mean when we call something "graphic"? In American Graphic, Rebecca Clark examines the "graphic" as a term tellingly at odds with itself. On the one hand, it seems to evoke the grotesque; on the other hand, it promises the geometrically streamlined in the form of graphs, diagrams, and user interfaces. Clark's innovation is to ask what happens when the same moment in a work of literature is graphic in both ways at once. Her answer suggests that the graphic turn in contemporary literature is intimately implicated in the fraught dynamics of identification. As Clark reveals, this double graphic indexes the unseemliness of a lust in our current culture of information for cool epistemological mastery over the bodies of others. Clark analyzes the contemporary graphic along three specific axes: the ethnographic, the pornographic, and the infographic. In each chapter, her explication of the double graphic hinges on pairing a canonical author--Edgar Allan Poe, Vladimir Nabokov, Thomas Pynchon--read against the grain with literary, visual and/or performance works by black and/or female creators--Mat Johnson, Kara Walker, Fran Ross, Narcissister, Teju Cole--in order to test the effects and affects of the double graphic across racialized and gendered axes of differences. American Graphic forces us to face how closely and uncomfortably yoked together disgust and data--identification with and identification of the other--have become in our increasingly graph-ick world"-- Provided by publisher
Keywords: American fiction -- History and criticism.; Grotesque in literature.; Affect (Psychology) in literature.; Aesthetics, American.; Roman américain -- Histoire et critique.; Grotesque dans la littérature.; Esthétique américaine.; Aesthetics, American; Affect (Psychology) in literature; American fiction; Grotesque in literature; Criticism, interpretation, etc.